Elaboration and technical specifications of the Peruvian pisco third stage-prototype plant - De La Cruz Azabache, Mario Ricardo (2013)
The present project in Applied Research has the objective to define the technical specifications of Peruvian Pisco, a traditional drink and patrimony, symbol of Peruvian pride and nationality. The importance of this project lies in the search for a higher standard of quality, composition and production for pisco elaboration in Peru, which is mostly artisanal and low technology. This design also involves obtaining a standardized process for elaboration of the grape liqueur denominated Pisco, with research trials at Prototype Reactor level, the development of a commercial product named Pisco UNI and obtaining an Invention Patent. Through a multidisciplinary group with the participation of professionals from the Facultad de Ciencias Biológicas de la Universidad Nacional de San Marcos; UNMSM; the Centro de Innovación de la Vid; CITEvid and Bodega y Viñedos La Caravedo de Ica; the obtained results were satisfactory, the standardized process guaranties the elaboration of a product of high quality and protected by an Invention Patent. The project also aims to provide technological innovation tools to students from Facultad de Ingeniería Química y Textil de la UNI; FIQT, that they can apply in their career development or creating their own business or work source, as a development alternative after they graduate.